Inhibition of Clostridioides difficile Toxins TcdA and TcdB by Ambroxol - Heber, Sebastian; Barthold, Lara; Baier, Jan; Papatheodorou, Panagiotis; Fois, Giorgio; Frick, Manfred; Barth, Holger; Fischer, Stephan (Frontiers in Pharmacology, 2022)
Clostridioides (C.) difficile produces the exotoxins TcdA and TcdB, which are the predominant virulence factors causing C. difficile associated disease (CDAD). TcdA and TcdB bind to target cells and are internalized via receptor-mediated endocytosis. Translocation of the toxins’ enzyme subunits from early endosomes into the cytosol depends on acidification of endosomal vesicles, which is a prerequisite for the formation of transmembrane channels. The enzyme subunits of the toxins translocate into the cytosol via these channels where they are released after auto-proteolytic cleavage. Once in the cytosol, both toxins target small GTPases of the Rho/Ras-family and inactivate them by mono-glucosylation. This in turn interferes with actin-dependent processes and ultimately leads to the breakdown of the intestinal epithelial barrier and inflammation. So far, therapeutic approaches to treat CDAD are insufficient, since conventional antibiotic therapy does not target the bacterial protein toxins, which are the causative agents for the clinical symptoms. Thus, directly targeting the exotoxins represents a promising approach for the treatment of CDAD. Lately, it was shown that ambroxol prevents acidification of intracellular organelles. Therefore, we investigated the effect of Ax on the cytotoxic activities of TcdA and TcdB. Ax significantly reduced toxin-induced morphological changes as well as the glucosylation of Rac1 upon intoxication with TcdA and TcdB. Most surprisingly, Ax, independent of its effects on endosomal acidification, decreased the toxins’ intracellular enzyme activity, which is mediated by a catalytic glucosyltransferase domain. Considering its undoubted safety profile, Ax might be taken into account as therapeutic option in the context of CDAD.